2014
DOI: 10.1016/j.virol.2014.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Coffee ringspot virus-Lavras: A model for an emerging threat to coffee production and quality

Abstract: The emergence of viruses in Coffee (Coffea arabica and Coffea canephora), the most widely traded agricultural commodity in the world, is of critical concern. The RNA1 (6552nt) of Coffee ringspot virus is organized into five open reading frames (ORFs) capable of encoding the viral nucleocapsid (ORF1p), phosphoprotein (ORF2p), putative cell-to-cell movement protein (ORF3p), matrix protein (ORF4p) and glycoprotein (ORF5p). Each ORF is separated by a conserved intergenic junction. RNA2 (5945nt), which completes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 65 publications
4
25
0
Order By: Relevance
“…7b in Martin et al, 2012). In this study, interaction between ADV N and P was also demonstrated by BiFC, where the location of the N:P complex was subnuclear, similar to that reported for SYNV, PYDV, CoRSV and OFV (Bandyopadhyay et al, 2010;Min et al, 2010;Kondo et al, 2013;Ramalho et al, 2014), but different to that observed for LNYV, which was in the cytoplasm . The BiFC results for ADV N and P proteins confirmed the earlier observed co-localization results for these proteins, and showed that the interaction was similar to that reported for these two proteins from nucleorhabdoviruses rather than cytorhabdoviruses.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…7b in Martin et al, 2012). In this study, interaction between ADV N and P was also demonstrated by BiFC, where the location of the N:P complex was subnuclear, similar to that reported for SYNV, PYDV, CoRSV and OFV (Bandyopadhyay et al, 2010;Min et al, 2010;Kondo et al, 2013;Ramalho et al, 2014), but different to that observed for LNYV, which was in the cytoplasm . The BiFC results for ADV N and P proteins confirmed the earlier observed co-localization results for these proteins, and showed that the interaction was similar to that reported for these two proteins from nucleorhabdoviruses rather than cytorhabdoviruses.…”
Section: Discussionsupporting
confidence: 87%
“…The interaction of N and P proteins is a common feature among not only the already characterized LNYV , PYDV (Bandyopadhyay et al, 2010) and SYNV (Min et al, 2010) but also the recently characterized dichorhaviruses coffee ringspot virus (CoRSV) (Ramalho et al, 2014) and orchid fleck virus (OFV) (Kondo et al, 2013), which have bipartite, negative-strand RNA genomes with clear sequence similarities to those of nucleorhabdoviruses, and the vertebrate rhabdovirus, vesicular stomatitis virus (VSV) (Moerdyk-Schauwecker et al, 2009; Fig. 7b in Martin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The N proteins of the nucleorhabdoviruses PYDV and maize fine streak virus (MFSV) also have an exclusive nuclear localization (Bandyopadhyay et al, 2010;Tsai et al, 2005), unlike N protein of the cytorhabdovirus lettuce necrotic yellows virus (LNYV), which is localized exclusively in the cell periphery as component of the cytoplasmic viroplasm (Martin et al, 2012). On the other hand, N proteins of the dichorhaviruses orchid fleck virus (OFV) and coffee ringspot virus (CoRSV) which are related to nucleorhabdoviruses, but have a bipartite genome, are distributed throughout the plant cell and imported into the nucleus through interactions with the exclusively nuclear P proteins (Kondo et al, 2013;Ramalho et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…P proteins of OFV and CoRSV are also exclusively nuclear (Kondo et al, 2013;Ramalho et al, 2014). For all nucleorhabdoviruses where viral protein localization and interactions have been studied, N and P proteins have been shown to interact and co-localize in the nucleus (Goodin et al, 2001(Goodin et al, , 2002Tsai et al, 2005;Bandyopadhyay et al, 2010;Martin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As a group, BTV affect, at least, 40 plant species ranging from major crops such as citrus and coffee, to economically important cultivated plants such as orchids and passion fruit, and other less significant ornamentals (Bastianel et al, 2010;Kitajima et al, 2010;Ramalho et al, 2014). The BTV-caused citrus leprosis is the main viral disease affecting citrus production in Brazil and is acknowledged to be re-emergent in the Americas (Roy et al, 2015).…”
Section: Introductionmentioning
confidence: 99%